Growth, maturation, and physical activity - Malina, Robert M.; Bar-Or, Oded; Bouchard, Claude (Champaign, IL Human Kinetics, 2004)
The second edition of Growth, Maturation, and Physical Activity has been expanded with almost 300 new pages of material, making it the most comprehensive text on the biological growth, maturation, physical performance, and physical activity of children and adolescents. The new edition retains all the best features of the original text, including the helpful outlines at the beginning of each chapter that allow students to review major concepts. This edition features updates on basic content, expanded and modified chapters, and the latest research findings to meet the needs of upper undergraduate and graduate students as well as researchers and professionals working with children and young adults. The second edition also includes these new features: 10 lab activities that encourage students to investigate subject matter outside of class and save teachers time; A complete reference list at the end of each chapter; Chapter-ending summaries to make the review process easy for students; New chapters that contain updates on thermoregulation, methods for the assessment of physical activity, undernutrition, obesity, children with clinical conditions, and trends in growth and performance; Discussions that span current problems in public health, such as the quantification of physical activity and energy expenditure, persistent undernutrition in developing countries, and the obesity epidemic in developed countries. The authors are three of the world's foremost authorities on children's growth and development. In 29 chapters, they address introductory concepts and prenatal growth, postnatal growth, functional development, biological maturation, influencing factors in growth, maturation and development, and specific applications to public health and sport. In addition, secular trends in growth, maturation, and performance over the past 150 years are considered. You'll be able to recognize risk factors that may affect young athletes; you'll also be able to make informed decisions about appropriate physical activities, program delivery, and performance expectations. Growth, Maturation, and Physical Activity, Second Edition, covers many additional topics, including new techniques for the assessment of body composition, the latest advances in the study of skeletal muscle, the human genome, the hormonal regulation of growth and maturation, clarification of dietary reference intakes, and the study of risk factors for several adult diseases. This is the only text to focus on the biological growth and maturation process of children and adolescents as it relates to physical activity and performance. With over 300 new pages of material, this text expertly builds on the successful first edition.
Undernutrition in Childhood and Adolescence ; Criteria ; Prevalence ; Forms of Undernutrition ; Undernutrition in Preschool Children ; Undernutrition in School-Age Children ; Long-Term Consequences of Undernutrition ; Summary ; Sources and Suggested Readings -- Chapter 24. Obesity in Childhood and Adolescence ; Indicators ; Criteria and Prevalence ; Correlates of Overweight and Obesity ; Consequences of Obesity for Children and Adolescents ; Long-Term Consequences of Obesity ; Treatment ; Summary ; Sources and Suggested Readings -- Chapter 25. Other Factors Affecting Growth, Maturation, Performance, and Activity ; Social Conditions, Growth, and Maturation ; Social Conditions, Motor Development, Performance, and Activity ; Ethnic Variation in Growth and Maturity ; Ethnic Variation in Motor Development, Performance, and Activity ; Climate, Growth, and Maturity ; Climate, Performance, and Physical Activity ; Summary ; Sources and Suggested Readings -- Part VI. Applications -- Chapter 26. Risk Factors During Growth and Adult Health ; Primary and Secondary Prevention ; Risk Factors for Common Metabolic Diseases ; Current Risk Profile of Children and Adolescents ; Summary ; Sources and Suggested Readings -- Chapter 27. Chronic Clinical Conditions and Physical Disabilities ; Selected Clinical Conditions That Affect Growth and Maturation ; Physical Activity of Children and Adolescents With Chronic Conditions ; Fitness and Performance of Children and Adolescents With Chronic Conditions ; Summary ; Sources and Suggested Readings -- Chapter 28. The Young Athlete ; Participation in Youth Sports ; Selection and Exclusion in Sport ; Who Is the Young Athlete? ; Stature and Weight of Young Athletes ; Maturity Status and Progress of Young Athletes ; Age at Menarche in Athletes ; Physique of Young Athletes ; Body Composition of Young Athletes ; Motor Performance Characteristics of Young Athletes ; Physiological Characteristics of Young Athletes ; Does Training for Sport Influence the Growth and Maturity of Young Athletes? ; Gymnastics and Ballet: Special Cases? ; Overview ; Summary ; Sources and Suggested Readings -- Chapter 29. Secular Trends in Growth, Maturation, and Performance ; Definitions ; Sources of Secular Trend Data ; Limitations and Assumptions in Secular Comparisons ; Secular Trends in Body Size ; Secular Trends in Body Proportions ; Secular Trends in Indicators of Maturity ; Secular Trends in Performance ; Secular Trends in Developing Countries ; Factors Underlying Secular Trends ; Summary ; Sources and Suggested Readings -- Suggestions for Individual and Group Activities -- Index -- About the Authors.
Includes bibliographical references
Keywords: Human growth; Exercise -- Physiological aspects